Drivers for Intermittent Water Supply in India: Critical Review and Perspectives - Ghorpade, Anujkumar; Sinha, Abhishek Kumar; Kalbar, Pradip P. (Frontiers in Water, 2021)
Intermittent Water Supply (IWS) is prevalent in most developing countries. Specifically, in India, IWS is existent throughout the country. Many studies focus on documenting the effects of IWS, and rarely the drivers of the IWS regime are studied. In this study, a systematic literature review was conducted on IWS studies around the globe. The various causes for IWS were documented. Then, by studying India’s typical water supply system (WSS) configuration, the vicious cycle of IWS in India is discussed. Further, the drivers of IWS were identified and elaborated with the causing mechanisms. This knowledge will help devise strategies and solutions for improving the IWS in India and other developing countries with similar socio-economic conditions.